Baclofen Solution for Low‐Volume Therapeutic Delivery. Issue 4 (3rd October 2016) - Meythaler, Jay M.; Peduzzi, Jean D.
Abstract : Objectives: Baclofen is a zwitterion molecule where increased ions in the excipient increase the solubility. We developed baclofen in a stable solution similar to cerebrospinal fluid (CSF) without bicarbonate and proteins to improve the solubility of the baclofen and to reduce the potential toxicity to the central nervous system (CNS) and subarachnoid space. The objective is to develop a solution of baclofen wherein baclofen is solubilized in a multivalent physiological ion solution such as artificial cerebrospinal fluid (aCSF) at a concentration from 2 mg/cc to 10 mg/cc. Methods: First, to determine the solubility of Baclofen in aCSF, solubility was determined at six different pH levels at 37°C, by the addition of aCSF to a known amount of Baclofen. The final concentrations were confirmed by high performance liquid chromatography (HPLC) analysis. Second, the stability of Baclofen at 4 mg/cc investigated in a test manufacturing batch utilizing standard methods of production of 1500 20 cc vials inverted for 18 months at 25°C at 60% humidity. The stability and purity of the baclofen was verified at 18 months by HPLC analysis. Results: Baclofen was initially soluble between pH of 6–8 above 7 mg/cc but fell back to 6.3–5.8 mg/cc level with time. Baclofen produced in vials with inversion were noted to be stable at 4 mg/cc at 18 months with less than 2% breakdown of the baclofen in solution. Conclusion: Baclofen is much more soluble in artificial CSF than normal saline. The artificial CSF may also be less toxic to the subarachnoid space than saline.